Digitalization of Agriculture and Its Impact on Productivity, Market Access, and the Digital Divide among Smallholder Farmers in Developing Countries: A Systematic Review Using the PRISMA Method - Karman, Tiara; Rahmawati; Faris Humam (Journal of Agri Socio Economics and Business, 2025)
The rapid expansion of digital technologies such as the Internet of Things (IoT), Artificial Intelligence (AI), and precision agriculture tools has transformed farming systems worldwide; however, their adoption among smallholder farmers in developing countries remains limited. This study aims to systematically review and synthesize empirical evidence on how digitalization in agriculture influences productivity, market access, and the rural digital divide. Using the PRISMA 2020 approach, fifty eligible articles published between 2020 and 2025 were analyzed qualitatively through thematic synthesis. The results reveal that digital adoption increases farm productivity by approximately 15–30% and enhances farmer income by 20–35%, mainly through improved market connectivity and data-driven decision-making. Yet, persistent gaps in digital literacy, infrastructure, and institutional support restrict equitable benefits among smallholders. The novelty of this research lies in the formulation of an integrated conceptual model linking digital adoption, market access, and welfare, with the digital divide identified as a moderating factor. The study concludes that digital agriculture can serve as a transformative driver for inclusive and climate-resilient rural development when accompanied by coherent policy interventions and digital capacity building.